Clinicopathological characteristics and prognosis of breast cancer patients with type 2 diabetes mellitus - HE, DE (Mol Clin Oncol, 2015)
Type 2 diabetes mellitus (T2DM) can increase the risk of several common cancers, including breast cancer (BC). The purpose of the present study was to investigate the clinicopathological features and prognosis of BC patients with or without T2DM. Seventy-eight patients were diagnosed with T2DM prior to the diagnosis of BC in the Cancer Hospital of Shantou University Medical College (Shantou, China) between 2002 and 2008. A total of 300 BC patients without T2DM were randomly selected as study controls during the same period. The clinicopathological characteristics, overall survival (OS) and disease-free survival (DFS) rates of these two groups were compared. Fifty-five BC patients and 133 control patients with T2DM were >50 years old (70.5 and 44.3%, respectively). There were more T2DM BC patients with body mass index (BMI) ≥25 kg/m(2) (46.2 vs. 23.3%) and these patients had a higher rate of lymph node involvement (67.9 vs. 55.0%). The DFS of the two groups was 32.1 vs. 22.3%. The OS of the two groups was 24.4 vs. 13.7%. Following adjustment for BMI, tumor-node metastasis stage and stratification of age, the relapse risk of T2DM BC patients was >2-fold higher than that of the control group in the estrogen receptor/progesterone receptor (ER/PR)-positive patients. In Her-2-negative BC patients, the relapse risk of T2DM patients was 2.237-fold higher than that of the non-T2DM patients. In conclusion, T2DM BC patients were significantly older and more likely to be overweight, and had more lymph nodes involvement. T2DM was associated with poor prognosis in ER/PR positive or Her-2-negative BC patients.